Robust PID controllers tuning based on the beetle antennae search algorithm - Spyridon D. Mourtas; Kasimis, Chrysostomos; Vasilios N. Katsikis (Memories - Materials, Devices, Circuits and Systems, 2023)
The core components of both traditional and contemporary control systems are the proportional–integral–derivative (PID) control systems, which have established themselves as standards for technical and industrial applications. Therefore, the tuning of the PID controllers is of high importance. Utilizing optimization algorithms to reduce the mean square error of the controller’s output is one approach of tuning PID controllers. In this paper, an appropriately modified metaheuristic optimization algorithm dubbed beetle antennae search (BAS) is employed for robust tuning of PID controllers. The findings of three simulated experiments on stabilizing feedback control systems show that BAS produces comparable or higher performance than three other well-known optimization algorithms while only consuming a tenth of their time.
Keywords: Beetle antennae search; Feedback control systems; Metaheuristics; Optimization; PID controller